Interaction Between Seed Treatment and Variety on Sudden Death Syndrome Symptoms and Soybean Yield - Eric Adee (Kansas Agricultural Experiment Station Research Reports, 2016)
Sudden Death Syndrome (SDS) is a soybean disease that perennially limits yields in the Kansas River Valley (KRV). The presence of soybean cyst nematode (SCN) and saturated soils has been implicated in contributing to the severity of the disease. Selecting varieties with some degree of tolerance to SDS has been the primary cultural practice to reduce yield loss to SDS. Another tool to reduce yield loss to SDS has been made available to growers with the release of ILeVO seed treatment from Bayer CropScience (Research Triangle Park, NC). The potential benefit of ILeVO on varieties with different levels of tolerance to SDS was examined in a study conducted at the Kansas River Valley Experiment Field in 2015. Five different soybean varieties that varied in tolerance to SDS were planted, with and without the ILeVO seed treatment. The study was irrigated as required for production. The SDS severity was less than previous years, with the most severely infested plots at just a little more than 20% of the leaf area expressing symptoms of SDS by the R6 growth stage. Treatments with ILeVO reduced the severity of SDS more and the yield increase was greater, up to 6 bu/a with varieties more susceptible to SDS.
Keywords: sudden death syndrome; soybean; seed treatment